Discrepancy of random graphs and hypergraphs. Issue 1 (8th November 2013) - Ma, Jie; Naves, Humberto; Sudakov, Benny
Abstract Answering in a strong form a question posed by Bollobás and Scott, in this paper we determine the discrepancy between two random k‐uniform hypergraphs, up to a constant factor depending solely on k. © 2013 Wiley Periodicals, Inc. Random Struct. Alg., 47, 147–162, 2015